PENINGKATAN HASIL BELAJAR KOGNITIF MENGGUNAKAN STRATEGI PEMBELAJARAN PROBLEM BASED LEARNING (PBL) PADA PEMBELAJARAN BIOLOGI DI KABUPATEN DELI SERDANG - Anggi Tias Pratama (Universitas Islam Negeri Sumatera Utara, 2018)
Cognitive learning results are one of the skills needed in a learning on the 21st Century in Biology learning. Empowerment of thinking and metacognitive skills needs to be done so that students become independent learners. This PBL strategy in learning is expected to help students to improve the ability of students' cognitive learning outcomes in Biology learning. This study aims to determine the improvement of cognitive learning outcomes of students taught with PBL strategies. The results showed that PBL strategies can improve students' cognitive learning outcomes in different abilities. Improvement of Cognitive Learning Outcomes of students in PBL strategies is 65.52% and conventional is 53.41%.